2012
DOI: 10.1105/tpc.112.096834
|View full text |Cite
|
Sign up to set email alerts
|

CDKF;1 and CDKD Protein Kinases Regulate Phosphorylation of Serine Residues in the C-Terminal Domain of Arabidopsis RNA Polymerase II

Abstract: Phosphorylation of conserved Y 1 S 2 P 3 T 4 S 5 P 6 S 7 repeats in the C-terminal domain of largest subunit of RNA polymerase II (RNAPII CTD) plays a central role in the regulation of transcription and cotranscriptional RNA processing. Here, we show that Ser phosphorylation of Arabidopsis thaliana RNAPII CTD is governed by CYCLIN-DEPENDENT KINASE F;1 (CDKF;1), a unique plant-specific CTD S 7 -kinase. CDKF;1 is required for in vivo activation of functionally redundant CYCLIN-DEPENDENT KINASE Ds (CDKDs), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 78 publications
(144 reference statements)
5
69
0
10
Order By: Relevance
“…The difference between CDKD;2 and CAK1 (or CDK7) was further shown by the discovery that CDKD;2 phosphorylates Ser-5 and Ser-2 of the Pol II CTD (Hajheidari et al, 2012). In this study, we found that cdkd;2 displayed an earlyflowering phenotype ( Figures 4C and 4D), whereas cdkc;1 and cdkc;2 exhibited a later-flowering phenotype (Cui et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…The difference between CDKD;2 and CAK1 (or CDK7) was further shown by the discovery that CDKD;2 phosphorylates Ser-5 and Ser-2 of the Pol II CTD (Hajheidari et al, 2012). In this study, we found that cdkd;2 displayed an earlyflowering phenotype ( Figures 4C and 4D), whereas cdkc;1 and cdkc;2 exhibited a later-flowering phenotype (Cui et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…P-TEFb phosphorylates the C-terminal domain (CTD) of Pol II at the Ser 2 site within the heptad repeats (26,29). This Ser 2 posttranslational modification orchestrates the interplay between transcriptional elongation and processing of mRNA (32)(33)(34)(35). This amino acid change in cdkc;2-3 is within the activation loop, known to be important for substrate binding, but not involved in interaction with the cyclin component of P-TEFb (Fig.…”
Section: Significancementioning
confidence: 99%
“…CDKA and CDKB are direct regulators of cell cycle transitions (Boudolf et al, 2004;Iwakawa et al, 2006). CDKD and CDKF are CDK activation kinases, which regulate the activities of other CDKs (Shimotohno et al, 2004;Umeda et al, 2005;Hajheidari et al, 2012). CDKC and CDKE are related to the transcriptional regulation of RNA polymerase II (Barrôco et al, 2003;Wang and Chen, 2004;Cui et al, 2007).…”
Section: Introductionmentioning
confidence: 99%